2011
DOI: 10.3892/or.2011.1566
|View full text |Cite
|
Sign up to set email alerts
|

MAGE A1-A6 RT-PCR and MAGE A3 and p16 methylation analysis in induced sputum from patients with lung cancer and non-malignant lung diseases

Abstract: The melanoma antigen gene (MAGE) A1-A6 RT-PCR system was developed for the detection of lung cancer cells in the sputum. However, we identified MAGE expression in some patients with non-malignant lung diseases. To understand these patterns of MAGE expression, we performed MAGE A3 methylation-specific PCR (MSP) and p16 MSP. We collected 24 biopsy specimens of lung cancer tissue and performed MAGE A1-A6 RT-PCR, MAGE A3 MSP and p16 MSP. RNA and DNA were simultaneously extracted from induced sputum specimens of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The median frequency of gene hypermethylation was higher in tumour than in sputum samples: 48% (interquartile range 36–64%) vs 38% (interquartile range 31–57%), respectively. A meta-analysis on exact data (Kersting et al , 2000; Liu et al , 2003; Wang et al , 2003; Olaussen et al , 2005; Shivapurkar et al , 2007; Shin et al , 2012) showed that this observed tendency was not significant ( P =0.09; Durkalski et al , 2003). Median concordance of methylation between tumour and matched sputum, calculated from the same studies, is 78% (interquartile range 73–91%), indicating that the use of sputum as non-invasive biological fluid for detection of aberrant methylation is representative of the methylation status of primary tumour tissue.…”
Section: Molecular Analysis Of Sputummentioning
confidence: 96%
See 1 more Smart Citation
“…The median frequency of gene hypermethylation was higher in tumour than in sputum samples: 48% (interquartile range 36–64%) vs 38% (interquartile range 31–57%), respectively. A meta-analysis on exact data (Kersting et al , 2000; Liu et al , 2003; Wang et al , 2003; Olaussen et al , 2005; Shivapurkar et al , 2007; Shin et al , 2012) showed that this observed tendency was not significant ( P =0.09; Durkalski et al , 2003). Median concordance of methylation between tumour and matched sputum, calculated from the same studies, is 78% (interquartile range 73–91%), indicating that the use of sputum as non-invasive biological fluid for detection of aberrant methylation is representative of the methylation status of primary tumour tissue.…”
Section: Molecular Analysis Of Sputummentioning
confidence: 96%
“…Concerning p16 gene, five studies (Belinsky et al , 1998; Destro et al , 2004; Olaussen et al , 2005; Cirincione et al , 2006; Shivapurkar et al , 2007) with ⩽55 PCR cycles and nine studies with >55 PCR cycles (Kersting et al , 2000; Palmisano et al , 2000; Konno et al , 2004; Belinsky et al , 2006; Hsu et al , 2007; Liu et al , 2008; Guzmán et al , 2012; Leng et al , 2012; Shin et al , 2012) with sensitivity and specificity data were available for bivariate analysis (Reitsma et al , 2005). Interestingly, mean specificity was shown to be significantly lower in the group of studies with >55 PCR cycles (74% vs 87%, P <0.001), whereas sensitivity was higher, but not significantly different (49% vs 33%, P =0.13).…”
Section: Molecular Analysis Of Sputummentioning
confidence: 99%
“…INK4a was identified in plasma and sputum samples of patients with early lung cancer, as well as in lung cancer tissue samples (27,28). These studies indicated that p16…”
Section: Discussionmentioning
confidence: 98%
“…Shin et al collected sputum from 133 patients with lung diseases (65 lung cancers and 68 benign lung diseases) and showed methylation abnormalities in patients with MAGE-positive sputum (in both malignant and benign diseases). Thus, MAGE expression in the sputum suggests the presence of lung cancer cells or pre-cancerous cells (51). …”
Section: Prognostic and Predictive Value Of Epigenetic Changesmentioning
confidence: 99%